Evaluating two international agreements for consistency with GATT/WTO rules: a methodological study with regard to EU/RSA trade, development and cooperation agreement and southern African development community agreements - Blignaut, C.S. (University of Pretoria, 2013)
Dissertation (MSc (Agricultural Economics))--University of Pretoria, 2007.